New doxorubicin-loaded phospholipid microbubbles for targeted tumor therapy: in-vivo characterization - Tinkov, Steliyan; Coester, Conrad; Serba, Susanne; Geis, Nicolas; Katus, Hugo; Winter, Gerhard; Bekeredjian, Raffi (Journal of controlled release, 2010)
Doxorubicin(DOX) is a potent chemotherapy drug that is often limited by severe adverse effects such as cardiac toxicity and myelosupression. Drug targeting with non invasive techniques would be desirable, aiming at increased local drug concentration and reduced systemic side effects. Ultrasound(US) targeted destruction of drug loaded microbubbles(MBs) has evolved as a promising strategy for non invasive local gene and drug delivery. A recently developed novel DOX-loaded microbubble (DOX-MB) formulation was previously tested in-vitro, with optimal DOX loading capacity, ideal physical characteristics and preserved antiproliferative efficacy. The aim of this study was to evaluate applicability and efficacy of DOX-loaded MBs in a pancreas carcinoma model of the rat. First, immediate toxicity was tested in rats ruling out in-vivo MB agglomeration/capillary adhesion with subsequent embolisation/occlusion of the pulmonary vasculature. In a second set of experiments, tumors derived from pancreas carcinomas were implanted in both flanks of Lewis rats. After establishing the tumors, DOX-MBs were administered intravenously while one of the two tumors was exposed to US (1.3MHz; mechanical index 1.6). DOX tissue concentration was measured in tumors and control organs after the experiment. Finally, efficacy of US targeted destruction of DOX-MBs in tumors was studied, looking at tumor growth after two therapeutic applications. All rats survived the DOX-MB administration without any sign of embolisation/occlusion of the pulmonary vasculature. US targeted destruction of DOX-MBs leads to a 12-fold higher tissue concentration of DOX and a significantly lower tumor growth in the target tumor compared to the contralateral control tumor. In conclusion, novel DOX-loaded MBs can be safely administered to rats, leading to a relevant increase in local drug concentration and reduction in tumor growth.